Impact of parity on cow stress, behavior, and production at a farm with guided traffic automatic milking system - Davis, Lindsey; French, Elizabeth A.; Aguerre, Matias J.; Ali, Ahmed (Frontiers in Animal Science, 2023)
The widespread adoption of advanced technology, like automatic milking systems in the United States, allows cows to establish individual milking, feeding, and resting schedules, setting them apart from others. However, it is unknown how cow parity affects cow behavior, stress, and system efficiency. We hypothesized primiparous (PR) cows would spend more time in and around the milking robot (AMS), receive greater agonistic interactions, and show elevated physiological stress behaviors compared to multiparous (MU) cows. The study aimed to evaluate the impact of cow parity on behavior and welfare near and inside the AMS. Twenty-four lactating-Holstein dairy cows (12 primiparous (3.0 ± 0.2 yr) and 12 multiparous (6.1 ± 1.9 yr)) housed in the same pen at a guided traffic AMS facility were marked and observed for 6-consecutive days (91 to 102 of lactation). Study cows were identified by specific colored-paint markings, their milk yield and visits, their behavior, Heart Rate-Variability (HRV), and activity were recorded inside the commitment pen (CP) and the AMS. Statistical calculations were performed using JMP Pro 16.1.0, and P≤0.05 was considered significant. Multiparous cows produced more daily milk yield than PP cows (47.30 Vs 33.79 kg), while parity showed no effect on daily milking frequency or milk yield per visit. Primiparous cows spent significantly more time inside the CP than MP cows (68.87 vs 24.38 m), while MP cows approached the AMS entry more often than the PR cows (4.83 vs 2.03), MU cows displaced other cows more inside the CP than PR cows (6.90 vs 2.59). PR cows showed lower HRV (RMSSD: 9.23 vs 17.58 ms) and (SDRR: 19.58 vs 33.64 ms) values than MU cows, whereas MU cows showed a lower Low-Frequency to High-Frequency Ratio (4.39 vs 8.65) than PR cows inside the CP. MU cows spent more time (m) lying (698.06), particularly at night (396.57), than PP cows (556.96, 286.68), while MP cows exhibited more prolonged total lying bouts than PP cows (93.06 vs 71.32 m). Overall, cow parity influenced behavior, activity, and stress indicators of primiparous more than multiparous cows and impacted the overall efficiency and success of the AMS INTRODUCTION